Argon plasma coagulation for successful treatment of bile leakage after subtotal cholecystectomy - Tsukasa Aritake; Kenji Takagi; Natsuki Nagano; Ryutaro Kobayashi; Takashi Maeda; Kiyotaka Kawai; Satoru Kawai; Satoaki Kamiya (Surgical Case Reports)
Abstract Background Subtotal cholecystectomy is an effective surgical method to decrease the risk of complications for gallbladders that are difficult to remove. However, there is a risk for postoperative refractory bile leakage through the gallbladder stump. Here, we report a new management technique involving the use of argon plasma coagulation (APC) to stop bile leakage after a subtotal cholecystectomy. Case presentation A 74-year-old man was referred to our hospital for abdominal pain and fever. Contrast-enhanced computed tomography of the abdomen showed fluid collection, such as an abscess, surrounding the gallbladder and hepatic flexure colon. The patient was diagnosed with colonic perforative peritonitis, and he underwent emergency surgery. On laparotomy, the abscess was observed outside of the hepatic flexure colon and gallbladder necrosis was detected. The neck of the gallbladder and the area close to the hepatoduodenal ligament was severely inflamed prohibiting dissection. The hepatic flexure colon was part of the abscess wall, and resection was needed. A subtotal cholecystectomy and right hemicolectomy confirmed peritonitis caused by cholecystic perforation. The mucous membrane of the gallbladder neck that remained was necrotic or detached. Therefore, the stump of the gallbladder was closed by primary sutures without cauterization of the mucosa. On postoperative day 6, bile leakage from the gallbladder stump was revealed. Percutaneous and endoscopic retrograde cholangiography drainage were performed. However, the liquid, which seemed to be secreted from the mucosa of the remnant gallbladder, was continuously obtained. We used APC to cauterize the gallbladder mucosa through the fistula of the abdominal drainage tube. Bile leakage and mucus discharge were improved after three rounds of APC cauterization. Conclusions APC effectively treated refractory bile leakage from a gallbladder stump after subtotal cholecystectomy for severe cholecystitis.